The industrial performance of wind power industry in China. (March 2015) - Liu, Yuanxin; Ren, Lingzhi; Li, Yanbin; Zhao, Xin-gang
Abstract: Wind power industry in China has experienced a rapid development from 2005 to 2010. However, in recent years, with the slowing down of growth in the new installed capacity, the competition among wind turbine manufacturers has become increasingly fierce. In order to comprehend the performance of wind power industry in China, in the article, we analyzed the status quo of wind power industry and the development process of wind power feed-in tariff in China, and then we used the Data Envelopment Analysis (DEA) model to analyze the performance of wind power industry from 2008 to 2012. According to the analysis result, we found that: (1) the performance of wind power generation industry is rising, and it has reached an optimal state in 2012. (2) In 2009 and 2010, the performance of wind turbine manufacturing industry was in the best state, but it started to decline from 2011. (3) The trends of performance of wind power generation industry and that of wind turbine manufacturing industry are not synchronized. The growth in installed capacity of wind power has an important influence on the performance of wind turbine manufacturing industry.